IS ZOMIA A USEFUL IDEA FOR INNER ASIA? (The Lattimore Lecture (2014), Ulaanbaatar, Mongolia) - CAROLINE HUMPHREY (Mongolian Journal of Anthropology, Archaeology and Ethnology, 2015)
James Scott’s idea of ‘Zomia’ – societies in Southeast Asia resisting the state and taking refuge in cross-border regions difficult for military access – is at first sight difficult to apply to Inner Asia. For Inner Asia has been under state rule for centuries. However, it has also had pockets of resistance and regionally specific economies. This article suggests that, if due attention is paid to historical and geographical specificity, the idea of ‘Zomia’ can be useful. It suggests a way to think about history that is not dominated by nation-state narratives, but instead explores regional irregularities, cross-border socio-cultural formations, and episodes when groups have attempted to build their own politics rather than subordinate themselves to a central state.